Clinical Utility of Qualitative Change of Direction Movement Assessment in ACL Injury Risk Evaluation - Evan Andreyo; Casey Unverzagt; Thomas Dos'Santos; J. Jay Dawes (International Journal of Sports Physical Therapy)
Anterior cruciate ligament (ACL) injuries are complex and influenced by numerous internal and external risk factors that should be considered to effectively mitigate injury and facilitate informed return to sport decision-making. Among these risk factors, movement quality exhibited during sport-specific tasks has been identified as a significant predictor of injury occurrence. Particularly, change of direction (COD) movements, when performed with sub-optimal movement quality, such as knee valgus and lateral trunk flexion, are prominent mechanisms of ACL injury in multidirectional sports. Unfortunately, the formal and objective assessment of COD movement quality is underutilized in clinical and sports practice, with existing methods often confined to expensive, sophisticated laboratory settings impractical for everyday clinicians. The purpose of this clinical commentary is to demonstrate the necessity of integrating COD movement assessments to screen for potential ACL injury risk, particularly among higher-risk populations. The authors will review cost-effective and clinic-friendly objective tests used to qualitatively screen COD movements, such as the Cutting Movement Assessment Score and The Expanded Cutting Alignment Tool. Additionally, this commentary will discuss key considerations when assessing COD movement.